Four-Year Follow-Up from a Prospective, Multicenter Study of Percutaneous 60-Day Peripheral Nerve Stimulation for Chronic Low Back Pain - Christopher A. Gilmore; Timothy R. Deer; Mehul J. Desai; Sean Li; Michael J. DePalma; Steven P. Cohen; Brandon D. Swan; Meredith J. McGee; Joseph W. Boggs (Pain and Therapy)
Abstract Introduction Chronic low back pain (LBP) is a leading cause of healthcare expenditure and long-term disability associated with complex treatment challenges and the need for progressively invasive interventions. Percutaneous 60-day Peripheral Nerve Stimulation (PNS) is a minimally invasive neurostimulation treatment that has shown efficacy for chronic LBP, providing sustained improvements through 1 year of follow-up after treatment. The present work explores the long-term clinical outcomes of Percutaneous 60-day PNS for chronic LBP approximately 4 years after initial treatment. Methods Follow-up surveys were sent to participants from a prior prospective study who reported clinically meaningful reductions in pain, disability, or pain interference 12 months after Percutaneous 60-day PNS for LBP. The present long-term follow-up survey assessed current levels of LBP, disability, pain interference, and Patient Global Impression of Change (PGIC). Use of medications and other interventions for LBP treatment since completing Percutaneous 60-day PNS was also surveyed. Results In total, 23 participants returned completed long-term follow-up surveys. A majority of survey respondents (65%, n = 15/23) reported sustained, clinically meaningful (≥ 30%) relief of back pain compared with baseline an average of 4.7 years after PNS treatment was initiated. On average, these long-term responders reported clinically substantial (≥ 50%) reductions in pain (average 63% reduction), as well as clinically meaningful improvements in disability and quality of life. Furthermore, 70% (n = 16/23) of survey respondents avoided progression to more costly, invasive, and/or destructive LBP pain interventions (i.e., radiofrequency ablation, neurostimulation implant, or lumbar surgery). Conclusions Treatment with Percutaneous 60-day PNS provided clinically meaningful pain relief among a majority of surveyed participants an average of more than 4 years after the short-term treatment. These results demonstrate that Percutaneous 60-day PNS can provide durable outcomes that are often sustained for multiple (4+) years by patients with chronic axial LBP who subsequently avoid the need for more invasive treatment interventions. Clinical Trial Registration The Clinicaltrials.gov registration number for the initial study is NCT03179202.